The principle of gender equality and its guarantee in the right to work. - Veloz, Javier; Ruiz Abril, Karina Marianela; Cabrera Vélez, Juan Pablo (Revista Universidad de Guayaquil, 2018)
The present work deals with the topic: "The principle of gender equality and its guarantee in the right to work." The work deals with the principle of equality, which consists of the equality of rights and opportunities for all human beings, it will include equality to work, which allows any person - without prejudice to their gender, ethnicity, socio-economic situation, etc. - access a job and be treated as equal.However, from the constant efforts of the legislation to guarantee equality at work and thus avoid discrimination, in practice there are cases of study that would be thought impossible, such as the one analyzed, which is about a worker who is fired of the fire department for being a woman, since at the discretion of the government entity, with the dismissal, she is protected from carrying out an activity intended only for men. It will be studied in the same way, the measures of integral reparation that the Constitutional Court of Ecuador, dictated against this violation of constitutional rights.The methodology to be used in the research is deductive, exploratory and descriptive. A qualitative approach will be used, as it is the one of the social sciences and more punctually of the Law.
Keywords: Constitutional law; extraordinary protection action; gender equality; discrimination based on sex; right to work; effective protection of rights